Characteristic rotational behaviors of rod-shaped cargo revealed by automated five-dimensional single particle tracking - Kuangcai Chen (Nature Portfolio, 2017)
Distinguishing rotational motions from translational motions in the z-axis has been a long-standing challenge. Here the authors develop a five-dimensional single particle tracking method to detect rotational behaviors of nanocargos during clathrin-mediated endocytosis and intracellular transport.